Pengaruh Dana Transfer terhadap Pendapatan Pajak dan Retribusi Daerah Kabupaten/Kota di Indonesia - Satria Tradinatama; Akhmad Solikin (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2023)
The provision of large amounts of transfer funds could affect the own-source revenues (Pendapatan Asli Daerah, PAD) collected by the regional governments, known as a crowding-out effect. Nevertheless, this theory is still debated, especially in developing countries, where transfer of funds is proven to increase the PAD, i.e. crowding-in effect. This study aims at analyzing whether the transfer funds in Indonesia consisting of General Allocation Fund (Dana Alokasi Umum, DAU), Revenue Sharing Fund (Dana Bagi Hasil, DBH), and Special Allocation Fund (Dana Alokasi Khusus, DAK) increase or decrease PAD, especially regional taxes and regional levies. Fixed effect panel data regression was implemented for regencies’/cities’ 2014-2017 data. Regression results show that the DAU reduces the amount of local taxes collected but increases regional retribution income. Conversely, the DBH increases local tax revenues but decreases regional retribution. Therefore, each type of transfer fund affects differently on tax and retribution income in districts/cities in Indonesia, i.e. both crowding-out and crowding-in are observed.